Clima urbano: análise do campo térmico e sugestão de áreas prioritárias para implementação de medidas mitigadoras - Lima Júnior, Antonio Ferreira (2023)
This research started from the hypothesis that understanding the thermal field of the city of Fortaleza results in relevant information to be used in city planning actions. Therefore, the main objective of this work was to indicate priority areas for the implementation of mitigating measures, in view of the diagnosis of the thermal field of the city of Fortaleza, in association with the characteristics of the surface. In order to fulfill the proposed objective, a statistical analysis of the climatic components of the city of Fortaleza was carried out, through the Mann-Kendall and Pettitt test, which evaluate the trend of alteration of the data series. The methodology used to understand the relationship between surface occupation and urban climate was the Urban Climatic Map, using georeferenced information in ArcGIS software to produce mappings and classification models of urban climate. Meteorological campaigns were carried out using sensors, where graphs and thermal spatialization maps were analyzed. Through the spatial autocorrelation method (Moran Index), it was possible to identify homogeneous spatial clusters, identifying the mildest and warmest áreas of the city. The UCMap reveals that a large part of the city of Fortaleza is inserted in a context of increased urban climate impact, due to the high built volume and the constructive characteristics used, however the proximity to the sea, the presence of vegetation and water bodies, makes with a high dynamic potential in several areas of the city. The analysis of the thermal field showed that the outskirts of the city of Fortaleza (northwest, west and southeast) register the highest values of air temperature, both in the dry season and in the rainy season, while green structures, such as Parque do Cocó are cool islands in the city environment. Spatial autocorrelation clusters were identified, both for the UCMap and for the air temperature data, where once again the northwest/west region presented na unfavorable situation, while the east of the city is under a greater dynamic potential.Therefore, the districts of Regional 1 and the Center are the ones that need to be prioritized in the implementation of actions and measures to mitigate adverse thermal effects.